Decoding the Architectural Geometry of Plaosan Temple: An Ethnographic Exploration for Contextual Mathematics Education - Michelia Putri, Karolyne; Ishartono, Naufal (Universitas Muhammadiyah Surakarta, 2026)
Student Many ethnomathematical studies in Indonesia have explored mathematical concepts embedded in cultural products such as batik, traditional houses, and other temple architectures. However, there has been little to no research specifically investigating the geometric aspects of Plaosan Temple as a cultural heritage site. Therefore, the current study aims to explore the geometrical concepts embedded in Candi Plaosan using an ethnographic approach. The study used ethnography as an approach by answering four principal questions, namely,